Penerapan Arsitektur Industrial Pada Lembaga Pemasyarakatan Kelas II A Di Kabupaten Barru - Ikhsan, Ikhsan; Rahayu, Irma; Alfiah, Alfiah (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2022)
Abstract_ The Barru City Detention Center always accepts the transfer of prisoners as a result of over-capacity of prisoners. Detainees from various surrounding areas, such as Maros, Pangkep Soppeng or from the Makassar Class I Penitentiary. The need for an adequate design of Correctional Institutions in terms of infrastructure facilities with an architectural style that is familiar with community life and building functions. Descriptive and exploratory design methods with an Industral Architecture approach. The design results are in the form of design drawings for class II A detention houses that apply Industrial Architecture.